Flow instabilities in a horizontal thermosyphon reboiler loop - Agunlejika, Ezekiel O.; Langston, Paul; Azzopardi, Barry J.; Hewakandamby, Buddhika N. (Elsevier, 2016)
Thermosyphon systems have been the subject of several studies due to instability issues negating their attractive high heat fluxes, low temperature gradients requirement, reduced weight and simple, pump-less system. There is a dearth of design data for horizontal thermosyphons hence the transient behaviour of a horizontal thermosyphon reboiler loop has been studied experimentally here. Most studies here have explored and defined geysering instability in single and parallel vertical columns with closed bottom end. This study presents geysering detected in 51 mm riser of a horizontal thermosyphon reboiler. Experiments were undertaken with water as the process fluid and steam as the heating medium, using 6 – 20 kW/m2 heat flux, 1.165 – 1.265 m static head and a range of recycle flow restrictions. Pressure, temperature and flow rate data were continuously logged at 100Hz. Flow rate was examined as a significant indicator of instability since it is the parameter with highest and varied amplitude of oscillation. Heat flux is most significant for stability: above 20 kW/m2, the system is stable; between 11 – 20 kW/m2 there are varying degrees of sustained oscillations and below 11 kW/m2 flow rate is low. Reboiler inlet flow restriction also stabilises the system by reducing the flow rate to such a level that heat transfer rate can maintain a consistent vapour product rate. Static head influences the recirculation rate and subcooling at the reboiler inlet, but has a secondary effect on stability. Churn flow pattern is detected in the riser as a characteristic aftereffect of the cyclic instability.